The effect of chitosan on enhancing the defense mechanisms of yard long bean plants against Aphis craccivora Koch. - Megasari, Dita; Santoso, Sugeng; Damayanti, Tri Asmira (Agrovigor, 2025)
Yard-long bean production in Indonesia has declined due to environmental factors and pest infestations, particularly by Aphis craccivora, a vector of viruses such as Bean common mosaic virus (BCMV). Generally, A. craccivora has been controlled using insecticides; however, their use poses limitations including toxicity, the development of resistance, environmental concerns, and disruption of pest–predator dynamics due to excessive application. As a promising alternative, chitosan has demonstrated potential in inhibiting aphid feeding, reducing reproduction rates, delaying disease incubation periods, and lowering BCMV titres. This study assessed the effects of both pure and commercial chitosan on A. craccivora in yard-long beans. The evaluation focused on antixenosis, antibiosis, and insecticidal properties. The results showed that chitosan significantly reduced aphid colonisation and feeding preference, lowered infestation intensity, and enhanced natural predation. Furthermore, chitosan treatments suppressed aphid reproduction, prolonged the aphid life cycle, and decreased their growth rate. The direct spray method was found to be more effective than the systemic application. Among the treatments, KK 0.9 consistently produced the most favourable outcomes across all parameters, indicating its potential as an effective bio-insecticidal agent for pest and disease management in yard-long bean cultivation.